PENERAPAN METODE GALLERY WALK PADA PELATIHAN APLIKASI SLEEKR ACCOUNTING BAGI KOPERASI DI KOTA BENGKULU - Siti Aisyah; Nila Aprilla; Fenny Marietza (Universitas Bengkulu, 2018)
This science-based community service’s activity aims to provide additional basic knowledge of cooperative accounting in order to assist SMEs accounting manager or staff in applying Sleekr Accounting through training and assistance for partners of cooperatives in the City of Bengkulu. The training was held for 2 days and attended by 16 partner cooperatives through the Bengkulu City Cooperatives and SMEs Office. Cooperative accounting training is carried out using the Gallery Walk active training method. This method is very useful for exploring participants' knowledge and making participants more active and focused on activities. From this training, participants were able to compile a standard account chart with in their group. Training in the use of sleekr accounting applications is delivered using a mixed method between lectures, discussions, and practices. From this training, participants can set-up early by using standard account chart data that they have compiled in the first day training. Keywords: Cloud Accounting, Cooperatives, gallery walk